2013
DOI: 10.1111/aor.12198
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extracorporeal Membrane Oxygenation Therapy on Systemic Oxidative Stress Injury in a Porcine Model

Abstract: Extracorporeal membrane oxygenation (ECMO) therapy can result in systemic immune inflammation and trigger a hemolytic response, both of which can lead to oxidative stress injury. However, currently, there are few studies about whether ECMO can lead to oxidative stress injury. The objective of this study was to determine the effect of ECMO therapy on systemic oxidative stress. Twelve pigs were randomly divided into control and ECMO treatment groups. Blood samples were collected at -1, 0, 2, 6, 12, and 24 h duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…When conventional medicine fails in these patients, ECMO is one of the few remaining life-saving options [4]. Previous ECMO studies in paediatrics [25], rabbits [26], lambs [27], sheep [28] and pigs [29] have shown significant elevations in lipid peroxides. However it is difficult to translate these findings to critically ill adult patients as (i) paediatric patients have significantly different bodyweight to ECMO surface area ratios and (ii) (with the exception of the sheep study [28]) in all the other animal models ECMO was initiated in a healthy host.…”
Section: Discussionmentioning
confidence: 99%
“…When conventional medicine fails in these patients, ECMO is one of the few remaining life-saving options [4]. Previous ECMO studies in paediatrics [25], rabbits [26], lambs [27], sheep [28] and pigs [29] have shown significant elevations in lipid peroxides. However it is difficult to translate these findings to critically ill adult patients as (i) paediatric patients have significantly different bodyweight to ECMO surface area ratios and (ii) (with the exception of the sheep study [28]) in all the other animal models ECMO was initiated in a healthy host.…”
Section: Discussionmentioning
confidence: 99%
“…This rescue therapy is used in severe ARDS when conventional mechanical ventilation fails [5, 38]. As ECMO has been shown to have pro-inflammatory effects in vivo [39, 40], it is conceivable that GILZ induction was aimed at compensating for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present results demonstrate that control group showed an increase in inflammatory markers in comparison to the sham group that can be explained by the ECMO itself applied for a duration of 20 hours. It is well known that ECMO over a long period of time causes systemic and organ inflammation (28). Therefore, it is even more interesting that the effect of Pao 2 oscillations on cerebral inflammation was superimposed to the deleterious effect of ECMO therapy.…”
Section: Cerebral Oxygen Oscillations Cause Neuroinflammationmentioning
confidence: 99%